Test of The Effectiveness of Kepok Banana Peel Extract Serum on Hair Growth in Guinea Pigs - Sihombing, Fenny Theresia; Chandra, Rudi; Oentari, Widyaningsih (Green Publisher Indonesia, 2025)
Hair plays an important role in supporting appearance and confidence, while hair loss is a common problem. In Indonesia, the prevalence of hair loss reaches 20% in adults and increases with age. Natural approaches such as Kepok banana peel extract, which is rich in antioxidants, flavonoids, and vitamins, are increasingly in demand as an alternative to hair care. This study aims to evaluate the effectiveness of Kepok banana peel extract serum on hair growth in guinea pigs. The method used was a laboratory experimental study with five treatment groups, namely Kepok banana peel extract serum with concentrations of 20%, 30%, 40%, negative Control, and positive Control (minoxidil® 5%). Each group consisted of five guinea pigs (n = 5), and observations were made over four weeks. The results showed that the 30% concentration of Kepok banana peel extract serum had the best effectiveness, with an average hair growth of 0.17814 ± 0.084711 g, close to the effectiveness of 5% minoxidil® (0.19124 ± 0.050439 g). Statistical analysis showed a significant difference between the negative Control and the 30% treatment (p = 0.003 in the third week). In conclusion, Kepok banana peel extract serum with a concentration of 30% has the potential to be an effective alternative to hair care